Curricular innovation and interdisciplinarity in action: a case study in secondary education - Rivas Albuquerque, Erick Mauricio; Romero Díaz , Miroslava; Malespín Miranda , Álvaro César (Scientific journal of social studies, 2024)
This study examines the implementation of Integrated Teaching Units (ITUs) at a Managua private school, addressing the Nicaraguan curriculum’s traditional structure, which is based on separate subjects and contents. The main goal was to analyze the experience of four secondary school teachers during a pilot test conducted in the second semester of 2022, using a qualitative approach and the case study method. The sources of information included the four teachers, documents from the design of the ITUs, meeting minutes, and classroom observation guides, utilizing semi-structured interview techniques and document analysis. The results revealed three main themes: teaching practices, interdisciplinarity, and the development of teaching competencies. Despite initial challenges and confusion among students, collaborative planning highlighted teaching practices that facilitated curricular integration, promoted transparency in evaluation, and improved student learning. Interdisciplinarity, although challenging, resulted in motivated students and enriched teachers through the incorporation of new elements into the classes. Additionally, strengthening of generic competencies among teachers was observed, thanks to joint planning and teamwork, enhancing communication and fostering trust.